DETERMINAN TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR - Haryo Suparmun; Natasya Joevanca (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
Tax is one of the largest sources of state revenue, the greater the tax revenue, the more it supports and builds a country's finances. However, for companies as taxpayers, taxes are a burden that can reduce company profits, therefore many companies do tax avoidance. Tax avoidance is one of the efforts made by taxpayers in avoiding taxes legally, namely minimizing the tax burden by exploiting the weaknesses of a country's tax laws. The purpose of this research is to examine the influence of profitability, leverage, company size, capital intensity, sales growth, independent commissioner, company age, and audit committee on tax avoidance. This research used 65 manufacturing companies listed on the Indonesia Stock Exchange as samples and the data were selected using the purposive sampling method during the research period from 2018 until 2020. Data is analyzed by using the multiple regression method with a significant level of 5%. The result indicates that profitability and leverage had a significant impact on tax avoidance. Profitability has a negative effect on ETR, so tax avoidance is carried out higher, while leverage has a positive effect on ETR, so tax avoidance is carried out lower. But, company size, capital intensity, sales growth, independent commissioner, company age, and audit committee had no significant impact on tax avoidance